Promoting the Use of Capital Markets for Infrastructure Financing : Lessons for Securities Markets Regulators in Emerging Market Economies - World Bank Group (World Bank, Washington, DC, 2018)
This Note provides guidance to securities markets regulators in emerging market economies (EMEs) about key regulatory issues that could affect the issuance of debt instruments for infrastructure financing over which they have some control. The Note focuses on three areas (placement regime, disclosure obligations and control issues in financing structures) and whether and how their regulation could affect the use of two debt financing instruments in EMEs, project bonds, and infrastructure debt funds. To this end, it has drawn from the experiences of a select number of countries in both advanced and emerging market economies to distill lessons that can be used by securities regulators in EMEs to tailor their regulatory frameworks so that they can support infrastructure financing. The choice of debt financing instruments stems from the fact that the most pressing need for EMEs is access to lower cost, longer-term debt which the two instruments discussed herein are likely to deliver.